Notes on Why Friends, Why Friendship into Poems - Thumboo, National University of Singapore, Edwin (Asiatic: IIUM Journal of English Language and Literature, 2013)
History is especially important in a nation that does not have a long past. For the writer who has to work in cross-cultural terms, the study of English Literature would have stressed the importance of a working history, tapped to provide a sense of context, location and continuity. This is the case with Singapore, which is without a direct historical hinterland. But because it is small, economically strong and politically stable, there is need for the writer to construct missing continuities. This he does by looking not only at the past, but also into the present, its multi-racial, multi-ethnic character. For the present case, friends are both the crystallisation and detailing of this precise historical context, essential for the penetration of both contemporary culture as well as their antecedents. They represent experience as well as repository, a combination that makes them excellent conduits. In the case of Singapore, these cultures mean for the writer specifically the Chinese, Indian, Malay and Eurasian.